Inhibitors of the Cdc34 acidic loop: A computational investigation integrating molecular dynamics, virtual screening and docking approaches - Arrigoni, Alberto (Elsevier, 2014)
Among the different classes of enzymes involved in the ubiquitin pathway, E2 ubiquitin-conjugating enzymes occupy a central role in the ubiquitination cascade. Cdc34-like E2 enzymes are characterized by a 12–14 residue insertion in the proximity of the catalytic site, known as the acidic loop. Cdc34 ubiquitin-charging activity is regulated by CK2-dependent phosphorylation and the regulatory mechanism involves the acidic loop. Indeed, the phosphorylation stabilizes the loop in an open conformation that is competent for ubiquitin charging. Cdc34 is associated with a variety of diseases, such as hepatocellular carcinomas and prostatic adenocarcinomas. In light of its role, the discovery of potential inhibitory compounds would provide the mean to effectively modulate its activity. Here, we carried out a computational study based on molecular dynamics, virtual screening and docking to identify potential inhibitory compounds of Cdc34, modulating the acidic loop conformation. The molecules identified in this study have been designed to act as molecular hinges that can bind the acidic loop in its closed conformation, thus inhibiting the Cdc34-mediated ubiquitination cascade at the ubiquitin-charging step. In particular, we proposed a pharmacophore model featuring two amino groups in the central part of the model and two lateral aromatic chains, which respectively establish electrostatic interactions with the acidic loop (Asp 108 and Glu 109) and a hydrogen bond with Ser 139, which is one of the key residues for Cdc34 activity.